The rural imaginary of the urban reader: the mythic dream of a house in the country - Silva, Gislene (Brazilian journalism research, 2009)
This research is an attempt, within a socio-anthropological approach, to understand an apparently common phenomenon: the dream many urban dwellers have of owning a house in the country. The investigation is carried out among readers of the Globo Rural magazine, a publication which specializes in agricultural matters. The subscribers live in the city of São Paulo and they do not own any kind of property in rural areas. The purpose of this study is to try to apprehend the motives of this imaginary vision, thus contributing to the debate on the relations between country and town, as well as to an understanding of the interaction between subjects and symbolic cultural products in contemporary urban daily life. Faced with the complex relationship between man and nature and the historical condition experienced in a metropolis at this turn of the century, it is perceived that when dreaming of a house in the country, urban readers of the magazine do not simply turn nostalgically to a rural past. In fact, they express their deep criticism of the civilizing model of urbanity in the metropolis at the present time, and, looking ahead, they imagine a better future away from the city in a rural environment, closer to nature, in a place with more solidarity, away from violence, heavy traffic, pollution, and therefore with improved quality of life.